Risk factors for in-stent restenosis in maintenance hemodialysis patients with central venous occlusive disease and biomechanical assessment of stents - Yang Yu; Yuqin Xiong; Tao Li; Jingyuan Zhou; Weijie Yan; Yan Xiong; Yu Chen; Ping Fu (SAGE Journals, 2022)
Objectives:
To investigate the risk factors and biomechanical mechanisms of in-stent restenosis (ISR) in central venous occlusive disease (CVOD).
Patients and methods:
This retrospective study consecutively included 77 maintenance hemodialysis (MHD) patients with CVOD who received the first percutaneous transluminal angioplasty with stenting (PTS) due to symptomatic CVOD in a tertiary hospital. The mean age was 59.7 ± 14.0 years, and 51.9% of patients were male. The clinical characteristics, occurrence of ISR and patency rates were recorded. Finite element method was applied to assess the biomechanical properties of stents.
Results:
Among 77 patients with a mean CVS score of 8.0 ± 2.8, 20.8%, 62.3%, and 16.9% of patients had the main vein of CVOD in the subclavian vein, brachiocephalic vein, and superior vena cava, respectively. A total of 72 (93.5%) patients received successful PTS treatment, for which the stents implanted were mainly Fluency covered stent (48.6%) and SMART bare stent (31.9%). During 15 (10–24)-months of follow-up, ISR occurred in 36.1% of the 72 patients. The primary and assisted primary patency rates at 6, 12, and 18 months were 78%, 56%, 42% and 95%, 90%, 87%, respectively. A prolonged dialysis vintage was an independent risk factor for ISR, yet the stent type or the main vein location was not correlated with ISR. Among three laser-engraving stents, the SMART stent was the best in terms of flexibility, stress, and strain on stents but worst in stress or strain on vessels. The Luminexx stent was the best in radial force and worst in stress or strain on stents. The Vici stent was the best in stress and strain on vessels and worst in radial force and flexibility.
Conclusions:
An unsatisfactory comprehensive biomechanical performance from configurations rooted in existing stents may account for the high incidence of ISR in CVOD.
Keywords: Cardiology